2011
DOI: 10.1021/jo102382r
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectronic Factors in the Stereoselective Epoxidation of Glycals and 4-Deoxypentenosides

Abstract: Glycals and 4-deoxypentenosides (4-DPs), unsaturated pyranosides with similar structures and reactivity profiles, can exhibit a high degree of stereoselectivity upon epoxidation with dimethyldioxirane (DMDO). In most cases, the glycals and their corresponding 4-DP isosteres share the same facioselectivity, implying that the pyran substituents are largely responsible for the stereodirecting effect. Fully substituted dihydropyrans are subject to a “majority rule,” in which the epoxidation is directed toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 56 publications
2
38
1
Order By: Relevance
“…[16] When the glycosylation of 11 and 32 using the boronic ester 34 was conducted, it was found that glycosylation at an axial 4-OH in 34 preferentially proceeded to give the a(1,4) glycoside 38 in 65 %y ield with high regioselectivity [a(1,4)/a(1,3) = 9.3:1] and excellent astereoselectivity (Scheme 2B). When the 1a,2aanhydrogalactose 35 [17] and 1a,2a-anhydroisomaltose 36 [8] were employed as glycosyl donors,t he glycosylations with 20 using 25 were found to proceed effectively to afford the a(1,4) glycosides 39 [18] and 40,r espectively,w ith good regio- When the 1a,2aanhydrogalactose 35 [17] and 1a,2a-anhydroisomaltose 36 [8] were employed as glycosyl donors,t he glycosylations with 20 using 25 were found to proceed effectively to afford the a(1,4) glycosides 39 [18] and 40,r espectively,w ith good regio- …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] When the glycosylation of 11 and 32 using the boronic ester 34 was conducted, it was found that glycosylation at an axial 4-OH in 34 preferentially proceeded to give the a(1,4) glycoside 38 in 65 %y ield with high regioselectivity [a(1,4)/a(1,3) = 9.3:1] and excellent astereoselectivity (Scheme 2B). When the 1a,2aanhydrogalactose 35 [17] and 1a,2a-anhydroisomaltose 36 [8] were employed as glycosyl donors,t he glycosylations with 20 using 25 were found to proceed effectively to afford the a(1,4) glycosides 39 [18] and 40,r espectively,w ith good regio- When the 1a,2aanhydrogalactose 35 [17] and 1a,2a-anhydroisomaltose 36 [8] were employed as glycosyl donors,t he glycosylations with 20 using 25 were found to proceed effectively to afford the a(1,4) glycosides 39 [18] and 40,r espectively,w ith good regio- …”
Section: Methodsmentioning
confidence: 99%
“…Glycosylations of 11 with several 1,3-diol sugar acceptors(16)(17)(18)(19)(20)u sing the corresponding glycosyl-acceptor-derived boronic ester catalysts 21-25.Reagents and conditions: a) 1a (0.2 equiv), toluene, reflux, 3h.Bz= benzoyl. Scheme 1.…”
mentioning
confidence: 99%
“…Even though this strategy proved to be feasible on large scale, 17 it still involves the handling and the storage of volatile peroxide and a good diastereoselectivity can be achieved in some cases only with cryogenic temperatures and extensive reaction time. 18 We were drawn to a recent report by Dondoni et al about the direct epoxidation of glycals with an in situ generated DMDO. 19 This more practical approach consists of a biphasic system (dichloromethane/water) and Oxone ® as the co-oxidant (Method B).…”
Section: Scheme 2 Stereoselective Synthesis Of β-C-glycosidesmentioning
confidence: 99%
“…It was concluded that the anomeric oxygen in 4-DPs contributed towards a stereoelectronic bias in facioselectivity, whereas the C(5) alkoxymethyl in glycals imparted a steric bias, which at times could compete with the stereodirecting effects from the other oxygen substituents. 301 The ab initio quantum-chemical method on the 6-31G** basis has been used to study the mechanism of selenium oxide and selenous acid oxidation of 6-methyluracil to orotic aldehyde. The mixed anhydride of acetic and selenous acids, which possessed high activity and steric accessibility in electrophilic attack on position 5 of the pyrimidine ring, was formed with a gain of energy.…”
Section: Other Oxidationsmentioning
confidence: 99%